Applying the National Assessment Model to Research on Rural Social Studies - Stanley E. Easton (Journal of Research in Rural Education, 1983)
National Assessment of Educational Progress (NAEP) is a census-like survey of the knowledge, skills, and attitudes of Amerian youth and young adults. In this paper the National Assessment model is described, the steps in applying it to research on rural schools are outlined, and a rationale for using it in research on rural social studies is presented. The approach presented in this paper is useful when one wishes to determine how a specific group of rural students performs on the NAEP social studies/citizenship objectives. The NAEP model will produce data which are descriptive of a target population and will permit comparison of local results with those of a representative national sample of rural students.